ANALISIS MEKANISME PEMUNGUTAN DAN EFEKTIVITAS RETRIBUSI PASAR DI KOTA BITUNG - Kaunang, Meivi M.; Kalangi, Lintje; Runtu, Treesje (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
One source of Regional Original Revenue is local taxes, regional levies and other legitimate local revenue management. Regional levies consist of 3 types of retribution, namely general service retribution, business service retribution and certain licensing retribution. Marketâs levies is one type of regional retribution that is included in general retribution whose collection must be in accordance with the existing operational procedure standards to support the realization of its acceptance. This study aims to determine the mechanism of marketâs levies collection and the level of effectiveness of marketâs levies in the city of Bitung. The research method used is qualitative descriptive analysis, by analyzing the collection mechanism and the effectiveness of marketâs levies. The results of the study show that the mechanism of collection of retribution is in accordance with the existing SOP and the achievement of its effectiveness is effective with an average level of 87.13%. Bitung city government can be better able to approach marketers for example by socializing marketâs levies regulations so that later can also support the realization ofÂ levies revenue.Keywords : Marketâs Levies, Collection Mechanisms and Effectiveness